Cruzar la frontera del encanto. Juan Rulfo en el sistema mundial de las letras. Crossing the Frontier of Enchantment. Juan Rulfo in the World-System of Literature - CHRISTIANE STALLAERT (Hermeneus, 2019)
Juan Rulfo, with his novel Pedro Páramo, is one of the pioneers of the so-called Latin American boom, a phenomenon that cannot be explained without taking into account the role of translation. Sixty years after publication this paper examines the role of translation in the journey of Juan Rulfo/Pedro Páramoto the center of the world-system of letters. The analysis, based on quantitative and qualitative dataframed within theories of the sociology of translation (Heilbron,1999; Casanova,1999), starts from the introduction of this author/work in Dutch, an intermediate or central language according to the classification of De Swaan (2001). From this vantage point,the position of Juan Rulfo to the upper level (super-central languages ) and lower level (peripheral languages ) is analyzed. The data show that although Juan Rulfo took time to conquer autonomy, he reached the very heart ofthe world-system of literature, becoming a literary model for future generations.